1989
DOI: 10.1176/ajp.146.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Observations of interactions of depressed women with their children

Abstract: Dysfunctional interactions between mothers with major affective disorders and their children may contribute to the children's high risk of disorder. This study investigated the behavior of mothers with recurrent unipolar depression, bipolar disorder, or chronic medical illness and of normal subjects toward their children during a directly observed conflict discussion task. In addition, lifetime history of depression, current mood, and chronic stress were investigated as predictors of maternal interaction. Unip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…This is more so because rejecting maternal parenting behavior is relatively more common in our society [45]; therefore, it may be important to educate the public about these abnormal parenting styles that are associated with an increased risk of offspring to develop psychopathology. This data is consistent with previous research findings which have indicated that parental psychopathology is associated with maladaptive parental behavior [11,29-32] which is also associated with increased risk of the children to develop psychopathology. Perceived rejecting maternal parental behavior was the only independent variable, where higher scores on the rejecting-ineffective parenting scale were associated with higher odds of MDD among the youth.…”
Section: Discussionsupporting
confidence: 93%
“…This is more so because rejecting maternal parenting behavior is relatively more common in our society [45]; therefore, it may be important to educate the public about these abnormal parenting styles that are associated with an increased risk of offspring to develop psychopathology. This data is consistent with previous research findings which have indicated that parental psychopathology is associated with maladaptive parental behavior [11,29-32] which is also associated with increased risk of the children to develop psychopathology. Perceived rejecting maternal parental behavior was the only independent variable, where higher scores on the rejecting-ineffective parenting scale were associated with higher odds of MDD among the youth.…”
Section: Discussionsupporting
confidence: 93%
“…Conflict Conversation (5 min) The Conflict Task was modeled on the task used by several research groups (e.g., Gordon et al 1989; Moore et al 2004; Siqueland et al 1996; Whaley et al 1999). Prior to collection of behavioral and physiology data, parents and children were asked independently to generate lists of conflict topics for the conflict task.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, whereas high parental sensitivity, that is, the ability to promptly respond to and correctly interpret the child's cues (Ainsworth, Blehar, Waters, & Wall, 1978), facilitates the development of the child's ability to control NA (Kopp, 1989), a more intrusive parenting style may lead to an increased level of NA (Belsky, Putnam, & Crnic, 1996). Further, mothers experiencing DS develop altered and potentially problematic patterns of interaction with their infant, resulting in a suboptimal parenting style (e.g., Cummings & Davies, 1994;Field, Healy, Goldstein, & Guthertz, 1990;Gordon et al, 1989;Tronick, 1989).…”
Section: Introductionmentioning
confidence: 99%